Field Survey of the Destroyed 17th–18th Centuries Objects of Industrial Heritage in the Urals - E. A. Kurlaev (Историко-географический журнал)
The article considers the formation of the industrial landscape on the territory of the Ural region. The Urals’ modern industrial landscapes are a clear reflection of the centuries-old activity of the Russian state in peopling and developing this area. However, to date, many destroyed industrial monuments have not become the objects of archaeological research and inventory, since they are not recognized as archaeological, and there are no appropriate methods for their search and study. Furthermore, they cannot be identified and described by specialists from other fields of science. There is an opinion that written information is capable of completely independently and fully covering the historical period, but while working with documents it becomes obvious that these sources cannot always replace archaeological research. In domestic textbooks, educational and methodological manuals on archaeology, no attention is paid to the study of the written era sites, and there are no methods for complex historical and archaeological research. The purpose of this work is to analyze the accumulated experience and formulate recommendations for the search, excavation and reconstruction of destroyed industrial monuments of the 17th – 18th centuries. Survey based on data from the written sources makes it possible to identify the location of the site, excavations – to replenish information about the layout, technical equipment of the enterprise. The complex of sources allows creating an animated model of the enterprise using a computer. It is noted that there are significant differences in the methods of search, excavation and reconstruction of sites of the historical period from traditional research procedures.